New Data about Distribution of Rare Plant Species in Donetsky Chain of Hills Territory (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
78 new locations of 28 regional rare plant species: Adoxa moschatelliana L., Anemone sylvestris L., Artemisia salsoloides Willd., Arum elongatum Steven, Asplenium septentrionale (L.) Hoffm., A. trichomanes L., Astragalus pubiflorus DC., A. henningii (Steven) Klokov, Centaurea rutenica Lam., C. tanaitica Klokov, Cerastium pseudobulgaricum Klokov, Chamaecytisus lindemanii (V.Krecz.) Klásková, Corydalis paczoskii N.Busch, Cystopteris fragilis (L.) Bernh., Gagea bohemica (Zauschn.) Schult. et Schult., Dianthus elongatus C.A. Mey., D. pallidiflorus Ser., Echium russicum J.F. Gmel., Iris halophila Pall., Jurinea centauroides Klokov, Hyacinthella pallasiana (Steven) Losinsk, Linaria macroura (M.Bieb.) M.Bieb, Muscari neglectum Guss. ex Ten., Petasites hybridus (L.) P.Gaertn., Mey. et Schreb., Physalis alkekengi L., Polygala cretacea Kotov, Scorzonera purpurea L., Viola cretacea Klokov are found in the Donetsky chain of hills in 2001-2005.
Keywords: flora, regional rare species, Donetsky chain of hills.